2019
DOI: 10.1111/acer.14065
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of Macrophage Migration Inhibitory Factor in Upstream Control of the Unfolded Protein Response After Ethanol Feeding in Mice

Abstract: Background: Macrophage migration inhibitory factor (MIF), a pluripotent immune regulator, is an emerging mediator in alcohol-related liver disease (ALD). MIF is associated with ALD progression through its chemokine-and cytokine-like activities.Methods: Mechanistic studies into the role of MIF in ethanol (EtOH)-induced liver injury were performed in Mif À/À mice and in C57BL/6J mice treated with a small-molecule MIF antagonist, MIF098, after Gao-Binge (acute-on-chronic) EtOH feeding, an EtOH feeding protocol as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
(81 reference statements)
1
22
0
Order By: Relevance
“…In the case of MIF-1, the fortuitous apposition of structural features shared by nonphysiologic enzymatic activity with those required for CD74 interaction (43) has prompted multiple efforts to identify tautomerase inhibitors that also block receptor activation (29,31,32). Several compounds have shown auspicious activity in preclinical models, including ISO-1 (27,44), MIF098 (45)(46)(47), and others (32,34,48). One small-molecule MIF antagonist that has advanced into clinical development is ibudilast, which was originally developed as a phosphodiesterase inhibitor but was discovered to inhibit MIF allosterically (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of MIF-1, the fortuitous apposition of structural features shared by nonphysiologic enzymatic activity with those required for CD74 interaction (43) has prompted multiple efforts to identify tautomerase inhibitors that also block receptor activation (29,31,32). Several compounds have shown auspicious activity in preclinical models, including ISO-1 (27,44), MIF098 (45)(46)(47), and others (32,34,48). One small-molecule MIF antagonist that has advanced into clinical development is ibudilast, which was originally developed as a phosphodiesterase inhibitor but was discovered to inhibit MIF allosterically (49).…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, the benzoxazol-2-one class of MIF-1 antagonists was reported, with MIF098 showing an IC 50 of 0.010 M (41). This orally bioavailable small-molecule inhibitor was further reported to block MIF-1 binding to the extracellular domain of CD74 to attenuate recruitment of the CD74 signaling coreceptor CD44, reduce downstream ERK1/2 phosphorylation (46), and inhibit MIF-dependent lung injury (45) and liver disease (47). The small-molecule 4-IPP, which acts a suicide substrate to covalently modify Pro-1 and inhibit MIF-1, has been reported recently to also react with Pro-1 of MIF-2 to inhibit MIF-2 tautomerization and biological activity (28).…”
Section: Editors' Pick: Selective Mif-2/d-dt Inhibitormentioning
confidence: 99%
“…Preclinical studies with CVC, a dual inhibitor of CCR2 and CCR5, have shown promising results, 82 and MIF098, an inhibitor of the pluripotent cytokine/chemokine MIF, is also a promising agent for reducing chronic ethanol-induced liver injury in mice. 52,158 As alternatives to strategies that directly break the cycle of proinflammatory cytokine and chemokine signaling, strategies that promote anti-inflammatory responses and hepatocyte regeneration are also of interest. The most well studied are strategies involving IL22, 156,159 which has been shown to be promising from the perspectives of safety and efficacy.…”
Section: Microbial Dysbiosis and Intestinal Barrier Functionmentioning
confidence: 99%
“…Preclinical studies with CVC, a dual inhibitor of CCR2 and CCR5, have shown promising results, 82 and MIF098, an inhibitor of the pluripotent cytokine/chemokine MIF, is also a promising agent for reducing chronic ethanol-induced liver injury in mice. 52 , 158 …”
Section: Immunological Mechanisms Of Aldmentioning
confidence: 99%
“…To further explore this phenomenon of increased neurogenesis at lower EtOH doses as it relates to neuroimmune systems in the brain, we focused here on the pro‐inflammatory chemokine Cxcl12 (also known as SDF‐1) and its primary receptor Cxcr4, which are shown to have a major role in processes of neurogenesis, influencing the proliferation, differentiation, and migration of neurons from neuroprogenitor cells shown predominantly in vitro (Hwang et al, 2019). In adult human subjects, EtOH and beer are found to stimulate Cxcr4 expression in peripheral tissue and increase circulating levels of Cxcl12 (Chiva‐Blanch et al, 2014; Poulsen et al, 2019), while prolonged withdrawal or abstinence causes a decrease in Cxcl12 plasma levels (Garcia‐Marchena et al, 2016). Although this EtOH‐induced upregulation of Cxcl12 and Cxcr4 has been recapitulated in vitro (Karim et al, 2013) and in adult rodents (Gil‐Bernabe et al, 2011), there is little evidence describing EtOH’s effects on this chemokine system in the embryo, with only our recent study in the rat providing evidence that prenatal EtOH exposure at a moderate dose stimulates the Cxcl12/Cxcr4 system in neurons and neuroprogenitor cells in the hypothalamus (Chang et al, 2020a).…”
mentioning
confidence: 99%